Efficient, sustainable and secure use of smart city resources - Karjalainen, Niko (My University, 2021)
The rapid advancement and increased use of technology has introduced the concept of smart cities, driving cities around the world towards developing a wide variety of smart systems, solutions and services. While these smart components provide improvements to various city operations, from increased resource efficiency and sustainability to general quality of life enhancements, they also introduce many challenges that must be dealt with in order to ensure future success. The purpose of this thesis is to determine the necessary measures both current and future smart cities should take in order to use their resources in an efficient, sustainable and secure manner. This was primarily achieved through extensive theoretical research, using a wide variety of information sources, from various scientific publications to different web-based resources. In addition, a simulated model of a smart waste management system was designed in this thesis in order to aid the development of the Salo smart city project. Resource efficiency and sustainability are integral to successful smart city implementations, as they ensure that smart cities can continue to prosper and develop more and more advanced solutions and services in the future. Consequently, the importance of solutions such as smart energy, smart waste management and smart mobility will only continue to increase in the future. Moreover, smart cities must be prepared to deal with various challenges presented by the use of advanced technologies and smart systems - from security, privacy and service availability to people- and ethics-related challenges. In the final parts of the thesis, the aforementioned topics were discussed from the perspective of the Salo smart city project. The use of different security measures and cheaper smart solutions, such as the smart waste recycling centre designed in the thesis, were given as recommendations to guide Salo towards a more resource efficient, sustainable and secure future.
Keywords: smart city, resource efficiency, sustainability, security, waste management, Arduino, Salo